Time For ‘Girl Dinner’ During ‘Brat Summer’ : A sociolinguistic analysis of the coverage and conversation surrounding slang words and language change in news articles - Hatula, Emmi (My University, 2025)
This thesis examines the coverage and conversation surrounding slang words and language change in news articles and online dictionaries. Communication in modern media and with selected words hold power and a single word can hold much more meaning than what first meets the eye and should not be taken merely by face-value. This study specifically examines the slang words ‘brat’ and ‘girl dinner’ through articles and online dictionaries. The examined articles come from CNN, National Geographic and The Guardian. The examined dictionaries are Collins Dictionary, Dictionary.com and Merriam-Webster. The chosen materials were examined through Critical Discourse Analysis with the aim to analyse aspects of the chosen slang words, such as dictionary definitions and what type of discussion they elicited in the articles. The findings showed that slang words were less likely to be added to dictionaries despite their current popularity due to their historically fleeting nature. The articles, whether it was to inform or to promote readership, handled slang in a manner that recognised the power that slang words hold. ‘Brat’ and ‘girl dinner’ showed typical slang word characteristics and appeared as examples of using words to take agency over ones’ actions. In addition to having individual and communal benefits, the interactivity of internet has made slang a tool of influence. Since the scope of this thesis was constricted, additional research around the topic could unveil meaningful findings that could further teach us about the way we communicate with one another.
Keywords: language in media, news articles, online dictionaries, slang, language change, critical discourse analysis